Pengaruh Kepemimpinan, Sistem Pengawasan, Dan Komitmen Karyawan Terhadap Kualitas Layanan Administrasi Perkantoran Di PDAM Kota Bekasi - Rifdah Amara Sari; Marsofiyati Marsofiyati (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
This study aims to analyze the influence of leadership, supervision system, and employee commitment on the quality of office administration services at PDAM Kota Bekasi. Effective administration services are an important factor in improving customer satisfaction and corporate image, especially in the public sector such as PDAM which is responsible for providing clean water services. This study uses a qualitative approach to explore the opinions and experiences of employees and PDAM management related to these variables. The results of the study are expected to provide a deep understanding of how transformational leadership, effective supervision systems, and employee commitment can interact with each other in creating high-quality services. These findings are also expected to help PDAM management in designing strategies to improve office administration services and provide a basis for policy makers in public sector management. This study provides benefits for PDAM management, employees, service users, and public policy makers by offering practical and theoretical insights to improve service quality.